Sudden cardiac death in young athletes - Makarov, L. (IntechOpen, 2020)
Sudden death (SD) is the most dangerous and irreversible outcome of diseases in clinical as well as in sports medicine. Between 1980 and 2011, the Sudden Death in Young Athletes Registry in the USA, which was developed based on mass media information, recorded 2406 cases of sudden death, which were observed in 29 diverse sports. In the USA 80% of all SD occurred in high school/middle school or collegiate student athletes, and 20% were engaged in organized youth, postgraduate. Statistical data vary greatly in different countries: SCD incidence rate in the USA is 7.47 and 1.33 per 1,000,000 exercising male and female school-age athletes, respectively, whereas in Italy, the rate is 2.6 cases in men and 1.1 in women per 100,000 individuals per year who are involved in active competitive sports. The European Heart Rhythm Association (EHRA) position paper concluded that as an overall estimate, 1-2 out of 100,000 athletes between of age of 12 and 35 years old die suddenly each year. It was shown that the risk of SCD is significantly higher in athletes than in nonathletes with the same heart condition in the general population, by more than five times for ARVC, 2.6 times for coronary artery disease, 1.5 times for myocarditis, and more than 2 times for cardiac conduction system diseases